Hubungan Disiplin Kerja Guru Sejarah Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran IPS Di SMP Negeri 4 Bolo - Nurjannah, Nurjannah; Munandar, Risky Aris; Julkarnain, Julkarnain (Jurnal Ilmiah Mandala Education (JIME), 2022)
The aim of this research is to find out the relationship between the work discipline of history teachers and student achievement. This type of research is quantitative research. The sample in this study was class VIII students, totaling 29 people. Data collection methods used are tests and questionnaires. It can be concluded from this research that there is a relationship between the work discipline of a history teacher and student achievement in social studies subjects at SMP Negeri 4 Bolo for the academic year 2021/2022. This can also be proven from the results of the analysis using the product moment correlation formula with rcount greater than rtable or 0.398> 0.367. It can be concluded that there is a relationship between teacher discipline and student achievement in social studies subjects at SMP Negeri 4 Bolo in the 2021/2022 academic year, with a moderate category. After being analyzed using the determinant coefficient formula, it is known that the magnitude of the relationship between the two variables is 15.84%. The next analysis is using the T-test formula with the aim of knowing it is significant, while the tcount is greater than ttable or 2.255>2.052, it can be concluded that the relationship between the two variables is significant.